Promoting excellence using a novel educational tool in the North of Scotland. Issue 1 (2nd January 2019) - Wood, Rose; Kilpatrick, Hollie; Sampson, Rod
ABSTRACT: The General Medical Council (GMC) sets the standards and requirements for the delivery of all stages of medical education and training in the United Kingdom (UK). Using a novel educational tool (the 'Digital Carousel'), we set out to determine to what extent current systems and process sit alongside standards as set out in GMC document 'Promoting excellence' and establish key foci of work going forward to promote excellence in the Caledonian-Rural track (CRT) General Practice Specialty Training (GPST) educational programmes by engaging key stakeholders in the process. The 'Digital Carousel' allowed a large group of participants (including the Deanery team, GPSTs and ESs) to eﬃciently collaborate views on how our current GP training programme reﬂects guidance in 'Promoting excellence' and on areas for development. There was a sense of 'working together' in identifying key priorities of work for 'our' GP training programme. The tool may have value in a variety of medical educational settings.